Aldrin Contamination in Ennore Estuary and Coastal Waters of Chennai, East Coast of India - Sundararajan, S.; Karthikeyan, R.; Prakash Jabakumar, Prince; Raghumaran, S. (Asian Journal of Chemistry, 2015)
The Ennore estuary and nearby coastal area is a typical environment in Chennai, East coast of India which was studied for presence of aldrin concentration in the coastal water. Samples were collected semi-diurnally from Ennore estuary and Chennai coast for 48 h. The concentration was determined by gas chromatography with electron capture detector. The aldrin concentration in Ennore estuary varied from 4.82 ± 0.13 to 21.88 ± 1.18 ng/L and 9.49 ± 0.28 to 52.75 ± 2.04 ng/L during the high and low tides respectively. In the nearby coastal waters, the concentration varied from 2.24 ± 0.24 to 4.51 ± 0.19 ng/L and 3.14 ± 0.13 to 5.32 ± 0.30 ng/L during the high and low tides respectively. There is a significant (P < 0.000) spatial variation of aldrin concentration in the Ennore estuary during low tide, while during high tide, the spatial variation in the concentration is altered and more or less uniform among the first 4 sites (WQE-1 to WQE-4). This indicated that the tide influences aldrin concentration as well as change in the spatial spreading. However, in Chennai coast, the spatial variation in aldrin concentration is very minimal at low tide whereas in high tide, concentration became uniform in all the sites except WQC-6. In both Ennore estuary and Chennai coast, between high and low tides showed significant (P < 0.05) difference in aldrin concentrations except WQC-2 in Chennai coast.